THE PORTRAYAL OF LINTANG AND HIS CONFLICTS IN ANDREA HIRATA'S LASKAR PELANGI: A FREUDIAN PSYCHOANALITICAL APPROACH - Ade Purna Nugraha, - (2010)
ABSTRACT This research paper, entitled "The Portrayal of Lintang and His Conflicts in Andrea Hirata's Laskar Pelangi: A Freudian Psychoanalytical Approach", attempts to portray the character of Lintang, conflicts he face, and derive interpretation from analysis. Therefore, this study investigates the events experienced by Lintang that are categorized on the basis of Freud's three components of human psyche-the id, the ego, and the superego. From the discussion, it is found that Lintang has to choose whether he keeps on continuing his education or taking care of his family after the death of his father. His id and ego are in conflict, but then he decides to take care of his family though he has become a pride in his school. For marginal people like Lintang, it is difficult to fulfill their needs because most of the time they, to use Freudian terms, resist the reality. 1. Main Supervisor: Sudarsono, M.I., M.A. NIP. 196607051994031004 2. Co-Supervisor: Nia Nafisah, S.S., M.Pd. NIP. 19710424200642001